Pyridinium Fluorochromate Oxidation of Salicylaldehyde in Acid Medium - Sekar, K.G.; Venkatapathy, M. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of salicylaldehyde by pyridinium fluorochromate has been studied in 90% acetic acid-water (v/v) medium. The reaction has unit dependence on each of the PFC, [H+] and zero order with respect to substrate. Effect of neutral salt, viz., NaCl shows the reaction to exhibit a negative salt effect. The rate of the reaction increases with increase in percentage of acetic acid. The reaction does not induce the polymerization of ethylacrylate. From the kinetic data obtained, the activation parameters have been calculated and a plausible mechanism has been proposed.